Molybdenum-doped cadmium zinc sulfide solid solution photocatalyst as well as preparation method and application thereof
The conversion of phenylethylene glycol into hydrogen and α-hydroxyacetophenone by molybdenum doping zinc-cadmium sulfide solid solution photocatalysts has solved the problems of high energy consumption and large carbon emissions in the prior art, and achieved the production of green hydrogen and green environmentally friendly organic synthesis.
Patent Information
- Application Number
- CN202411746132.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-02
AI Technical Summary
In the prior art, hydrogen production and fine chemical synthesis have problems such as high energy consumption, large carbon emissions, and industrial hydrogen production depends on traditional non-renewable energy.
Molybdenum-doped zinc-cadmium sulfide solid solution photocatalyst is used to convert the cheap organic raw material phenylethylene glycol into hydrogen and the high value-added chemical α-hydroxyacetophenone through sunlight irradiation.
It has achieved organic synthesis of green hydrogen production and green environmental protection, with high efficiency catalysis, high selectivity, no side reactions and impurities generation, and mild reaction conditions, and easy to produce on a large scale.
Smart Images

Figure CN119588381A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts containing molybdenum sulfides, and in particular relates to a molybdenum-doped zinc cadmium sulfide solid solution photocatalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen plays a vital role in the current and future energy structure due to its many advantages such as high energy density and green and pollution-free. However, the current hydrogen production technology is still limited to industrial by-product hydrogen production, coal and natural gas hydrogen production and other models that rely on traditional non-renewable energy sources, resulting in a large amount of carbon emissions. The water electrolysis hydrogen production technology has extremely high costs and cannot be expanded to large-scale production. Therefore, it is necessary to study more economical hydrogen production methods.
[0003] In addition, traditional synthesis methods in the field of fine chemical synthesis cannot escape from harsh conditions, such as high temperature and high pressure, strong oxidants and reductants, etc., which result in high energy consumption and large carbon emissions.
[0004] Based on this, the present invention proposes a molybdenum-doped zinc cadmium sulfide solid solution photocatalyst, which is used to convert the cheap organic raw material phenyl glycol into hydrogen and high value-added chemical α-hydroxyacetophenone in a next step under sunlight irradiation, while realizing green hydrogen production and green and environmentally friendly organic synthesis, and has huge commercial application potential. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a molybdenum-doped zinc cadmium sulfide solid solution photocatalyst and a preparation method and application thereof in view of the deficiencies in the prior art. The photocatalyst can convert the cheap organic raw material phenyl glycol into hydrogen and high value-added chemical α-hydroxyacetophenone in a next step under sunlight irradiation.
[0006] The present invention provides a molybdenum-doped zinc cadmium sulfide solid solution photocatalyst, wherein the molybdenum-doped zinc cadmium sulfide solid solution photocatalyst is composed of Mo doped Zn 0.3 Cd 0.7 The S matrix is obtained, and the Mo doping amount is 1-6% of the total molar amount of Zn and Cd.
[0007] Preferably, the doping amount of Mo is 2.5-3.5% of the total molar amount of Zn and Cd.
[0008] The present invention also provides a preparation method of the above-mentioned molybdenum-doped cadmium zinc sulfide solid solution photocatalyst, and the specific steps are as follows: cadmium acetylacetonate (Cd(acac)2), zinc acetylacetonate (Zn(acac)2) and molybdenum oxyacetonate (MoO2(acac)2) are added to ethylene glycol, heated and stirred to dissolve to obtain a mixed solution, and then thioacetamide is added to the obtained mixed solution, and after stirring evenly, a solvent thermal reaction is carried out. After the reaction is completed, the solid product is separated and purified to obtain the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst.
[0009] According to the above scheme, the molar ratio of cadmium acetylacetonate, zinc acetylacetonate and molybdenum acetylacetonate is 8-50:8-50:1.
[0010] According to the above scheme, the mass volume ratio of cadmium acetylacetonate to ethylene glycol is 0.015-0.016 g / mL.
[0011] According to the above scheme, the heating stirring dissolution temperature is 90-110°C and the time is 30-60 minutes.
[0012] According to the above scheme, the molar ratio of cadmium acetylacetonate to thioacetamide is 1:2.2-2.7.
[0013] According to the above scheme, the solvent thermal reaction temperature is 170-190°C and the time is 1-3 hours.
[0014] The present invention also includes the use of the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst in the photocatalytic dehydrogenation reaction of aromatic diols to prepare hydrogen and aromatic alcohol ketones.
[0015] Specifically, the present invention includes the use of the above-mentioned molybdenum-doped cadmium zinc sulfide solid solution photocatalyst in the photocatalytic dehydrogenation reaction of phenyl glycol to prepare hydrogen and α-hydroxyacetophenone.
[0016] According to the above scheme, the specific application method is: dissolve phenyl glycol in an organic solvent, then add the above molybdenum-doped zinc cadmium sulfide solid solution photocatalyst, mix evenly (inert gas is introduced into the system to remove air), and carry out photocatalytic reaction under sunlight irradiation conditions.
[0017] The reaction formula is as follows:
[0018]
[0019] Preferably, the mass ratio of the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst to phenyl glycol is 1:0.7-1.4.
[0020] Preferably, the organic solvent is anhydrous acetonitrile, and the mass volume ratio of the phenyl glycol to the organic solvent is 1.25 to 1.75 mg / mL.
[0021] Preferably, the photocatalytic reaction time is 60 to 90 minutes.
[0022] The present invention uses an appropriate amount of Mo doped Zn 0.3 Cd 0.7 The Mo-doped solid solution nanophotocatalyst is obtained. The Mo-doped sites and the in-situ formed Zn vacancies constitute atomically dispersed active defect clusters, which not only enhance the photogenerated carrier separation rate but also provide a large number of atomic-level catalytic active sites, thereby improving the synthesis efficiency of hydrogen production and the generation of α-hydroxyacetophenone. The reaction has high selectivity, no side reactions and impurity generation, and can efficiently catalyze the acceptor-free dehydrogenation of the organic substrate phenylethylene glycol under simulated sunlight, and simultaneously obtain hydrogen and high value-added chemical α-hydroxyacetophenone.
[0023] The beneficial effects of the present invention are as follows: 1. The molybdenum-doped zinc cadmium sulfide solid solution photocatalyst provided by the present invention can form Mo-based atomic-level defect clusters with extremely high adsorption and catalytic activity, thereby significantly improving the adsorption activation of aromatic diols, and accelerating the catalytic dehydrogenation reaction to produce hydrogen and aromatic alcohol ketones. The photocatalytic efficiency is extremely high, and the aromatic diols can be converted into hydrogen and high-value-added chemicals aromatic alcohol ketones by a catalytic reaction in the next step of sunlight irradiation. When the reaction time is 60 to 90 minutes, the conversion rate of the substrate aromatic diol can be as high as 100%, and the selectivity of the product aromatic alcohol ketone is good, up to 100%, that is, no side reactions occur. 2. The preparation method provided by the present invention has simple steps, mild reaction conditions, and is easy to scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a field emission scanning electron microscope image of the molybdenum-doped zinc cadmium sulfide solid solution photocatalyst prepared in Example 2 of the present invention;
[0025] Figure 2 A spherical aberration-corrected high-angle annular dark-field image of the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst prepared in Example 2;
[0026] Figure 3 Element distribution diagram of the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst prepared in Example 2;
[0027] Figure 4 X-ray diffraction patterns of the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst prepared in Example 2 and the non-molybdenum-doped cadmium zinc sulfide solid solution photocatalyst prepared in Comparative Example 1;
[0028] Figure 5 The Raman spectra of the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst prepared in Example 2 and the non-molybdenum-doped cadmium zinc sulfide solid solution photocatalyst prepared in Comparative Example 1;
[0029] Figure 6A comparison chart of the photocatalytic activities of the molybdenum-doped zinc cadmium sulfide solid solution photocatalysts prepared in Examples 1-3 and the zinc cadmium sulfide solid solution photocatalysts not doped with molybdenum in Comparative Example 1;
[0030] Figure 7 This is a comparison chart of high performance liquid chromatography of the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst prepared in Example 2 at different photocatalytic reaction times. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below using embodiments in conjunction with the accompanying drawings.
[0032] Comparative Example 1
[0033] The preparation method of the non-molybdenum-doped zinc cadmium sulfide solid solution photocatalyst is as follows:
[0034] 0.3106 g Cd(acac)2 (1 mmol) and 0.2636 g Zn(acac)2 (1 mmol) were added together into a 50 mL single-necked flat-bottomed flask containing 20 mL ethylene glycol, heated to 100 °C using an oil bath, and mixed for 30 min at a magnetic stirring rate of 500 rpm until completely dissolved to obtain a white mixed solution, and then 0.1880 g thioacetamide (2.5 mmol) was added to the obtained mixed solution to obtain an orange-yellow turbid dispersion, which was then heated to 180 °C at a magnetic stirring rate of 500 rpm and kept warm for 1 h to further A sufficient solvent thermal reaction was carried out to obtain a yellow reaction liquid. After the reaction was completed, the temperature was naturally lowered for 30 minutes, and then the reaction liquid was high-speed centrifuged (10000rpm, 5min / time) with a high-speed centrifuge. After discarding the supernatant, ultrasonic washing was performed with a mixture of 15mL ultrapure water and 15mL anhydrous ethanol. The centrifugal washing steps were repeated 5 times, and then the obtained solid product was placed in a vacuum drying oven and vacuum dried at 60°C for 24h. After drying, it was ground for 5min to obtain a zinc cadmium sulfide solid solution photocatalyst without molybdenum doping.
[0035] Example 1
[0036] A molybdenum-doped zinc cadmium sulfide solid solution photocatalyst, the specific steps of the preparation method are as follows:
[0037] 0.3106 g Cd(acac)2 (1 mmol), 0.2636 g Zn(acac)2 (1 mmol) and 0.0058 g MoO2(acac)2 (0.02 mmol) were added into a 50 mL single-necked flat-bottomed flask containing 20 mL ethylene glycol, heated to 100 °C using an oil bath, and mixed at a magnetic stirring rate of 500 rpm for 30 min until completely dissolved to obtain a white mixed solution, and then 0.1880 g thioacetamide (2.5 mmol) was added to the obtained mixed solution to obtain an orange-yellow turbid dispersion, and then the dispersion was heated to 180 °C at a magnetic stirring rate of 500 rpm and kept warm for 1 h to perform sufficient solvothermal reaction to obtain a light brown reaction solution. After the reaction is completed, the single-mouth flat-bottom flask is immediately taken out and placed in ice water to cool for 30 minutes, and then the reaction solution is centrifuged at high speed (10000rpm, 5min / time) in a high-speed centrifuge. After discarding the supernatant, ultrasonic washing is performed with a mixed solution of 15mL ultrapure water and 15mL anhydrous ethanol. The centrifugal washing steps are repeated 5 times, and then the obtained solid product is placed in a vacuum drying oven and vacuum dried at 60°C for 24h. After drying, it is ground for 5min to obtain a molybdenum-doped zinc cadmium sulfide solid solution photocatalyst. The Mo doping amount in the photocatalyst obtained in this embodiment is 1% of the total molar amount of Zn and Cd.
[0038] Example 2
[0039] A molybdenum-doped zinc cadmium sulfide solid solution photocatalyst, the specific steps of the preparation method are as follows:
[0040] 0.3106 g Cd(acac)2 (1 mmol), 0.2636 g Zn(acac)2 (1 mmol) and 0.0196 g MoO2(acac)2 (0.06 mmol) were added into a 50 mL single-necked flat-bottomed flask containing 20 mL ethylene glycol, heated to 100 °C in an oil bath, and mixed at a magnetic stirring rate of 500 rpm until completely dissolved for 30 min to obtain a white mixed solution, and then 0.1880 g thioacetamide (2.5 mmol) was added to the obtained mixed solution to obtain an orange-yellow turbid dispersion, which was then heated to 180 °C at a magnetic stirring rate of 500 rpm and kept warm for 1 h to perform sufficient solvothermal reaction to obtain a light brown dispersion. The reaction liquid was immediately taken out of the single-mouth flat-bottom flask after the reaction was completed and placed in ice water to cool for 30 minutes, and then the reaction liquid was centrifuged at high speed (10000rpm, 5min / time) with a high-speed centrifuge. After discarding the supernatant, ultrasonic washing was performed with a mixture of 15mL ultrapure water and 15mL anhydrous ethanol, and the centrifugal washing steps were repeated 5 times. Subsequently, the obtained solid product was placed in a vacuum drying oven and vacuum dried at 60°C for 24h. After drying, it was ground for 5min to obtain a molybdenum-doped zinc cadmium sulfide solid solution photocatalyst. The Mo doping amount in the photocatalyst obtained in this embodiment is 3% of the total molar amount of Zn and Cd.
[0041] like Figure 1 Shown is a field emission scanning electron microscope image of the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst prepared in this embodiment. It can be seen from the figure that the photocatalyst is an agglomerate formed by nanoparticles with uniform particle size of about 10nm, and the diameter of the particle aggregates ranges from 50 to 500nm.
[0042] Figure 2 and Figure 3 They are respectively the spherical aberration-corrected high-angle annular dark field image and element distribution map of the molybdenum-doped zinc cadmium sulfide solid solution photocatalyst prepared in this embodiment, Figure 2 It can be seen from the figure that there are atomic-level defect clusters (coupled by heteroatom Mo and Zn vacancies) in the photocatalyst nanoparticles. Figure 3 It can be seen that Mo is evenly dispersed in the entire photocatalyst nanoparticles in small amounts, while Zn, Cd, and S are evenly distributed in the entire photocatalyst nanoparticles in large amounts.
[0043] Figure 4 From the X-ray diffraction patterns of the molybdenum-doped zinc cadmium sulfide solid solution photocatalyst prepared in this embodiment and the non-molybdenum-doped zinc cadmium sulfide solid solution photocatalyst prepared in Comparative Example 1, it can be found that, compared with the undoped sample, the characteristic diffraction peaks of the molybdenum-doped zinc cadmium sulfide solid solution photocatalyst prepared in this embodiment have not changed, indicating that the molybdenum-doped sample has good lattice stability.
[0044] Figure 5 The Raman spectra of the molybdenum-doped zinc cadmium sulfide solid solution photocatalyst prepared in this embodiment and the non-molybdenum-doped zinc cadmium sulfide solid solution photocatalyst prepared in Comparative Example 1 are shown. By comparing with Comparative Example 1, it is found that the molybdenum-doped zinc cadmium sulfide solid solution photocatalyst prepared in this embodiment shows the stretching vibration signal of the Mo-S bond, indicating the successful incorporation of the molybdenum element.
[0045] Example 3
[0046] A molybdenum-doped zinc cadmium sulfide solid solution photocatalyst, the specific steps of the preparation method are as follows:
[0047] 0.3106 g Cd(acac)2 (1 mmol), 0.2636 g Zn(acac)2 (1 mmol) and 0.0392 g MoO2(acac)2 (0.12 mmol) were added into a 50 mL single-necked flat-bottomed flask containing 20 mL ethylene glycol, heated to 100 °C in an oil bath, and mixed at a magnetic stirring rate of 500 rpm until completely dissolved for 30 min to obtain a white mixed solution, and then 0.1880 g thioacetamide (2.5 mmol) was added to the obtained mixed solution to obtain an orange-yellow turbid dispersion, and then the dispersion was heated to 180 °C at a magnetic stirring rate of 500 rpm and kept warm for 1 h to perform sufficient solvothermal reaction to obtain The light brown reaction liquid was taken out of the single-mouth flat-bottom flask immediately after the reaction was completed and placed in ice water to cool for 30 minutes, and then the reaction liquid was centrifuged at high speed (10000rpm, 5min / time) with a high-speed centrifuge. After discarding the supernatant, it was ultrasonically washed with a mixture of 15mL ultrapure water and 15mL anhydrous ethanol, and the centrifugal washing steps were repeated 5 times. Subsequently, the obtained solid product was placed in a vacuum drying oven for vacuum drying. After drying, it was ground for 5 minutes to obtain a molybdenum-doped zinc cadmium sulfide solid solution photocatalyst. The Mo doping amount in the photocatalyst obtained in this embodiment is 6% of the total molar amount of Zn and Cd.
[0048] Application Examples
[0049] The activity test method of photocatalytic dehydrogenation of phenyl glycol to produce hydrogen and α-hydroxyacetophenone by molybdenum-doped cadmium zinc sulfide solid solution photocatalyst is as follows:
[0050] 0.03 g of molybdenum-doped zinc cadmium sulfide solid solution photocatalyst, 0.0332 g of reaction substrate phenyl glycol and 20 mL of anhydrous acetonitrile were placed in a quartz glass reaction container with a total volume of 621 mL. The reaction container was then kept at a constant temperature of 0 ° C and evacuated for 10 min. Argon gas was then introduced to 80 kPa and the reaction container was kept at a constant temperature of 25 ° C. A 300 W xenon lamp with an AM 1.5 G bandpass filter was then used for illumination testing. The light source intensity was 100 mW / cm2 (simulating a standard sunlight intensity), the illumination distance was 10 cm, and the illumination time was 1 h. After the illumination, the gas product was sampled by an online gas chromatograph for 600 μL of hydrogen quantitative detection, and the liquid product was sampled by a high performance liquid chromatograph for qualitative and quantitative detection after the catalyst was filtered out.
[0051] Figure 6 The photocatalytic activity comparison diagram of the molybdenum-doped zinc cadmium sulfide solid solution photocatalyst prepared in Examples 1-3 and the zinc cadmium sulfide solid solution photocatalyst not doped with molybdenum in Comparative Example 1 shows that the photocatalytic dehydrogenation activity of phenyl glycol of the molybdenum-doped zinc cadmium sulfide solid solution photocatalyst prepared after molybdenum doping modification in Examples 1 to 3 is improved, and the molybdenum-doped zinc cadmium sulfide solid solution photocatalyst prepared in Example 2 performs best. Specifically, under the catalysis of the photocatalyst prepared in Example 2, the conversion rate of phenyl glycol reached more than 90% within 1h, the precipitation rate of hydrogen and α-hydroxyacetophenone reached more than 215μmol / h (stoichiometric ratio close to 1), and the effective ratio of photogenerated electron holes was close to 1, which also shows that it has the best activity of dehydrogenation of phenyl glycol to produce hydrogen, and the carbon balance is about 100%, indicating that the catalytic process does not obtain other by-products, and the selectivity of α-hydroxyacetophenone is 100%. These results indicate that the optimal Mo doping amount for Mo-doped ZnCdS solid solution photocatalyst is 3% of the total molar amount of Zn and Cd.
[0052] Figure 7 The HPLC comparison chart of the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst prepared in Example 2 at different reaction times under the above conditions shows that no other by-products are produced during the reaction, and the selectivity of the product α-hydroxyacetophenone is 100%.
Claims
1. A molybdenum-doped cadmium zinc sulfide solid solution photocatalyst, characterized in that: The molybdenum-doped zinc cadmium sulfide solid solution photocatalyst is composed of Mo doped Zn 0.3 Cd 0.7 The S matrix is obtained, and the Mo doping amount is 1-6% of the total molar amount of Zn and Cd.
2. The molybdenum-doped cadmium zinc sulfide solid solution photocatalyst according to claim 1, characterized in that: The doping amount of Mo is 2.5-3.5% of the total molar amount of Zn and Cd.
3. A method for preparing the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst according to claim 1 or 2, characterized in that: The specific steps are as follows: adding cadmium acetylacetonate, zinc acetylacetonate and molybdenum acetylacetonate to ethylene glycol, heating and stirring to dissolve to obtain a mixed solution, then adding thioacetamide to the obtained mixed solution, stirring evenly and then performing a solvothermal reaction, and after the reaction is completed, separating and purifying the solid product to obtain a molybdenum-doped cadmium zinc sulfide solid solution photocatalyst.
4. The method for preparing the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst according to claim 3, characterized in that: The molar ratio of cadmium acetylacetonate, zinc acetylacetonate and molybdenum acetylacetonate is 8-50:8-50:
1.
5. The method for preparing the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst according to claim 3, characterized in that: The mass volume ratio of the cadmium acetylacetonate to ethylene glycol is 0.015-0.016 g / mL.
6. The method for preparing the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst according to claim 3, characterized in that: The heating and stirring dissolution temperature is 90-110°C and the time is 30-60 minutes.
7. The method for preparing the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst according to claim 3, characterized in that: The molar ratio of cadmium acetylacetonate to thioacetamide is 1:2.2-2.
7.
8. The method for preparing the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst according to claim 3, characterized in that: The solvent thermal reaction temperature is 170-190°C and the time is 1-3 hours.
9. Use of the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst as claimed in claim 1 or 2 in the photocatalytic dehydrogenation reaction of aromatic diols to prepare hydrogen and aromatic alcohol ketones.
10. Use of the molybdenum-doped cadmium zinc sulfide solid solution photocatalyst according to claim 1 or 2 in the photocatalytic dehydrogenation reaction of phenyl glycol to prepare hydrogen and α-hydroxyacetophenone, characterized in that: The specific application method is: dissolving phenyl glycol in an organic solvent, then adding the molybdenum-doped zinc cadmium sulfide solid solution photocatalyst, mixing evenly, and performing a photocatalytic reaction under sunlight irradiation conditions.
Citation Information
Patent Citations
Non precious metal laden photocatalyst containing cuprum doped with sulfureous, zincium and vestalium as well as preparation method thereof
CN101176846A
Metal or metalloid modified zinc cadmium sulfide-ethylenediamine photocatalyst and preparation method
CN106582876A
Phosphorus-doped cadmium zinc sulfide solid solution catalyst, photocatalytic system and method for producing hydrogen through water decomposition
CN107790160A
Method for preparing diphenylethanone from benzyl alcohol through photocatalytic one-step method
CN108440259A
ZCS@Ni-MOF nanocomposite material and preparation and application thereof
CN108855222A